2021
DOI: 10.1007/jhep02(2021)095
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion interactions and lattices in chiral magnets: analytical results

Abstract: We study two-body interactions of magnetic skyrmions on the plane and apply them to a (mostly) analytic description of a skyrmion lattice. This is done in the context of the solvable line, a particular choice of a potential for magnetic anisotropy and Zeeman terms, where analytic expressions for skyrmions are available. The energy of these analytic single skyrmion solutions is found to become negative below a critical point, where the ferromagnetic state is no longer the lowest energy state. This critical valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The absolute ground states of the model are, unfortunately, not among these special states. Ross et al [26] extended these efforts beyond the exactly solvable point. They showed that two skyrmions interact via a repulsive potential decaying as a power of the distance.…”
Section: Historical Notementioning
confidence: 99%
“…The absolute ground states of the model are, unfortunately, not among these special states. Ross et al [26] extended these efforts beyond the exactly solvable point. They showed that two skyrmions interact via a repulsive potential decaying as a power of the distance.…”
Section: Historical Notementioning
confidence: 99%
“…In addition, it also opens up interesting ways to study the dynamics of vortex and skyrmion field configurations on spin lattices in various dimensions (for recent approaches, see, e.g., Refs. [51,[66][67][68][69]). We leave this for future work.…”
Section: Discussionmentioning
confidence: 99%
“…[29] that there are subtle contributions from infinity (the boundary) to the energy of the skyrmion (hedgehog) solutions in the case of two-dimensional chiral magnets along the solvable line 2A = B. Subsequently it has been realized that the additional total derivative term in the energy density is needed to make the variational principle well-defined, in deriving the field equations for the skyrmion [31].…”
Section: Boundary Termsmentioning
confidence: 99%
“…In the two dimensional solvable case, the boundary energy functional gives a finite and crucial negative energy contribution to the skyrmion energy. This fact leads to the instability of the polarized ferromagnetic background solution and a phase transition to other phases, such as the skyrmion lattice phase, below the critical value of potential parameters [31].…”
Section: Boundary Termsmentioning
confidence: 99%
See 1 more Smart Citation